A short review on biodiesel production and costing - Mirus, Muhammad Farhan; Nasir, Nurul Fitriah; Taib, Ishkrizat; Hariri, Azian; Nordin, Normayati; Mat Isa, Norasikin (Penerbit Akademia Baru, 2019)
Biodiesel has been introduced to reduce the dependency on fossil fuel. It is derived from vegetable oil, alcohol with the presence of a catalyst. One of the most significant issues in biodiesel market is the selling price. This paper will review the research conducted on the production of biodiesel, including the equipment, raw materials and cost. These three elements are crucial to reduce the price and enable biodiesel to be a competitive alternative fuel in the market. This paper also discusses recent developments in production, market values and suggestions for improving the biodiesel process. The results presented in this review may facilitate improvements in biodiesel production and costing.